2020
DOI: 10.3389/fbloc.2020.00022
|View full text |Cite
|
Sign up to set email alerts
|

Climate Crises and Crypto-Colonialism: Conjuring Value on the Blockchain Frontiers of the Global South

Abstract: This commentary explores how climate crises are used to justify "crypto-colonialism," whereby blockchain technology is used to extract economic benefits from those suffering the scars of historic colonial expansion in the Global South. These benefits include land, labor, data and other resources needed to facilitate capital interests elsewhere. As with past neoliberal development agendas imposing structural economic reforms, the contemporary crypto-colonial exercises discussed here are driven in pursuit of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…In the engineering world of code, standardized rules translate into 16 Such are the neoliberal economics encoded in crypto-currency projects that some observers have started to argue that blockchain technologies are being introduced to intently advance the neoliberal agenda in the Global South. They call these efforts a "new form of crypto-colonialism" (see Crandall, 2019;Howson, 2020). algorithms programmed ex-ante (Rozas et al, 2018), before communities are even given the opportunity to articulate their priorities and idiosyncrasies.…”
Section: Conclusion: Democratic or Despotic Money?mentioning
confidence: 99%
“…In the engineering world of code, standardized rules translate into 16 Such are the neoliberal economics encoded in crypto-currency projects that some observers have started to argue that blockchain technologies are being introduced to intently advance the neoliberal agenda in the Global South. They call these efforts a "new form of crypto-colonialism" (see Crandall, 2019;Howson, 2020). algorithms programmed ex-ante (Rozas et al, 2018), before communities are even given the opportunity to articulate their priorities and idiosyncrasies.…”
Section: Conclusion: Democratic or Despotic Money?mentioning
confidence: 99%
“…Manmade greenhouse gas emissions are the main cause of global warming, which will increase by 2.8°by 2050 if no action is taken in this decade [79]. The author in [79] emissions from forests [80], [81]. The authors analyzed several flaws of REDD+ and found solutions in blockchain technology, such as cryptocarbon management, green finance, and sustainable investments.…”
Section: ) Climate Protectionmentioning
confidence: 99%
“…Conversely, it is important to be cognisant of the potential surge of crypto-colonial practices in global health and international development in line with past colonial and neo-colonial activities that advance capital interests abroad. 11 This may present itself as green investments, investment inequalities and power asymmetry as a result of data colonialism. Despite being a distributed ledger, blockchain may thus not be full without geography if not configured appropriately.…”
Section: Cryptocurrenciesmentioning
confidence: 99%